The Extended Theory of Planned Behavior: Understanding Intention to Use Public Transportation Through Culture Based Public Transportation : In A Review - Prima Widayanto (ABNUS Publisher, 2023)
From the results of the elaboration of twelve articles and the existence of problems and the purpose of this article in the form of a review of articles related to the SDGs model by adding culture-based public transportation variables using the SOR model approach to the SDGs model. The formation of culture-based public transportation variables as a research update is based on the background of multi-cultural public transportation users in Indonesia, namely users with different backgrounds, needs, and preferences.